Undergraduate nursing students' experiences of becoming a professional nurse: a longitudinal study - Susanne Lundell Rudberg; Margareta Westerbotn; Taina Sormunen; Max Scheja; Hanna Lachmann (BMC, 2022)
Abstract Background During education it is essential for nursing students to develop professionalism in nursing. Nurses are placed in situations based on trust, and it is crucial that their patients have confidence in them to provide professional and safe care. A key period in nursing students' development of a professionalism occurs during training when students gain knowledge and skills that separate nurses as professional healthcare workers from laypeople. The purpose of this study was to investigate nursing students' experiences of professional competence development during education. Methods A longitudinal study was carried out using qualitative content analysis with a manifest inductive approach. Thirty-four students enrolled in a Swedish three-year nursing program, from August 2015 to January 2017 were interviewed on four occasions. Results The results revealed that students' professional role developed gradually. The students' started their education with dreams and a naive understanding of the profession, but their understanding of the complexity of the nursing profession gradually evolved. Students became theoretically equipped at the university and developed clinical skills through practice. Students' focus went from mastering medical technology to a more holistic approach. Before graduating, students felt ready but not fully trained. Conclusions Our findings indicate a discrepancy between the content of the theoretical education and the clinical settings since students identified a lack of evidence-based practice. A solid theoretical education before entering clinical training offered students possibilities for reflecting on evidence-based practice and the clinical settings. The realization that there is always potential for professional improvement can be interpreted as an emerging awareness, and development of professionalism. It is clear that students could benefit from increased collaborative work between clinical supervisors and faculty staff at the university.